2018
DOI: 10.3389/fphar.2018.01268
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effects of Benzyl Isothiocyanate and Resveratrol Against Cisplatin-Induced Oxidative Stress and Inflammation

Abstract: This study was performed to compare the nephroprotective effects of benzyl isothiocyanate (BITC) and resveratrol (RES) and investigate the nephroprotective efficacy of their combination against cisplatin-induced acute renal injury. Five animal groups (each of eight) received either normal saline, a single intraperitoneal injection of cisplatin (20 mg/kg) at the sixth day, cisplatin plus oral RES (30 mg/kg) or BITC (100 mg/kg in diet), or a combination of both for 10 days. Compared to saline-treated mice, cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 48 publications
5
26
0
Order By: Relevance
“…The cell membranes consist of lipids as its main component, and thus LPO can lead to cell damage and apoptosis. The peroxidation stage leads to the formation of MDA and the presence of MD in the cells confirms radically induced LPO . The present study stated an increase in MDA concentration in the renal cells in the case of BPA‐induced rats, thus confirming the condition of OS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The cell membranes consist of lipids as its main component, and thus LPO can lead to cell damage and apoptosis. The peroxidation stage leads to the formation of MDA and the presence of MD in the cells confirms radically induced LPO . The present study stated an increase in MDA concentration in the renal cells in the case of BPA‐induced rats, thus confirming the condition of OS.…”
Section: Discussionsupporting
confidence: 81%
“…Nrf2 then translocates to the nucleus and binds to the ARE . This binding causes the downstream activation of HO‐1 . The present study stated enhanced nuclear accumulation of Nrf2 by triptolide in case of the reperfused kidney.…”
Section: Discussionsupporting
confidence: 54%
“…In general, antioxidants stabilize cell membranes (particularly, neuronal membranes) by counteracting lipid peroxidation . Antioxidant substances are plant extracts such as chard, spirulina platensis, resveratrol, cinnamon, grape seed, melatonin, quercetin, and others. All these antioxidants have proved their beneficial protective role against tissues, lipid peroxidation, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other ITC members, BITC has immunomodulatory, anti-microbial, and anti-oxidative activities under various pathological conditions [34,65,66] Several studies have also shown that BITC possesses anti-cancer and chemopreventive effects in various types of malignancies [67][68][69]. However, there is limited information on its anti-cancer effects and molecular mechanisms in UC.…”
Section: Benzyl Isothiocyanatementioning
confidence: 99%